KEPASTIAN HUKUM KEPEMILIKAN SURAT IZIN GANGGUAN BIDANG USAHA MUSIC ENTERTAINMENT ATAU MUSIC STADIUM DITINJAU BERDASARKAN PERATURAN GUBERNUR NOMOR 101 TAHUN 2013 (STUDI PUTUSAN: PUTUSAN MAHKAMAH AGUNG NOMOR 2430K/PDT/2018) - Indi Bintang; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2019)
One of legal issue of business licensing occur in the Supreme Court Decision Number 2430 K/Pdt/2018 which basically contains a civil dispute between the Management of PT Wahana Agung Indonesia Propertindo (WAIP) with PT Mata Elang International Stadium (MEIS). In the judge's legal considerations, PT MEIS was declared default because during the holding of the concert / event in the room rented from PT WAIP, they still didn/t have the nuisance permit. But in their legal considerations, the Panel of Judges wasn’t careful enough in determining the legal basis. Then how is the legal certainty regarding to the possession of the nuisance permit in the field of music stadium business? How does the Government play a role in a way to overcoming uncertainty in the aspects of business licensing nowadays? To answer both questions, the author uses a normative research method, supported by statute approach and case approach. Legal certainty has not been achieved because there is an inaccuracy because the Panel of Judges didn’t consider the Governor Regulation of the Jakarta Special Capital Region Number 101 of 2013 which is an implementation instruction from Regional Regulation of the Jakarta Special Capital Region Number 15 of 2011. wherein the Governor Regulation of the Jakarta Special Capital Region Number 101 of 2013 further stipulates the terms of business locations that require a nuisance permit and concerning the nuisance criteria referred to in both of the legal regulations, and when referring to the provisions regarding the business location and the nuisance criteria referred to, PT MEIS doesn’t require an nuisance permit in conducting their business.